2009
DOI: 10.1097/meg.0b013e32832b2107
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two schemes of small bowel preparation for capsule endoscopy with polyethylene glycol: a prospective, randomized single-blind study

Abstract: The two schemes were equal regarding enteric cleansing and completion of the procedure. Therefore, 2 l seems to be an adequate preparation for capsule endoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 20 publications
0
33
0
5
Order By: Relevance
“…PEG solutions are non-absorbable and osmotically active and have been widely used in capsule endoscopy based on its ability to move through the bowel and potentially distend the lumen, wash out debris and bile, and possibly enhance small bowel transit time. The optimal dose of PEG that needs to be administered before SBCE is not entirely clear but 2 L appears to be sufficient [21][22][23] . A recent study concluded that the ingestion of a small amount of PEG after the swallowing of an endoscopy capsule significantly improved CE image quality, but did not enhance the completion rate to the cecum [24] .…”
Section: C B Amentioning
confidence: 99%
“…PEG solutions are non-absorbable and osmotically active and have been widely used in capsule endoscopy based on its ability to move through the bowel and potentially distend the lumen, wash out debris and bile, and possibly enhance small bowel transit time. The optimal dose of PEG that needs to be administered before SBCE is not entirely clear but 2 L appears to be sufficient [21][22][23] . A recent study concluded that the ingestion of a small amount of PEG after the swallowing of an endoscopy capsule significantly improved CE image quality, but did not enhance the completion rate to the cecum [24] .…”
Section: C B Amentioning
confidence: 99%
“…Positive findings were identified in nine patients from group A (23), nine from group B (20), and 12 from group C (25) ( Table 3). Suspicious findings were noted in four patients from group A, four from group B, and five from group C. The detection rates for definite and suspicious lesions in groups A, B, and C were 56.6, 65, and 68%, respectively, which seems to indicate that the more preparation is carried out, the more lesions can be detected.…”
Section: Resultsmentioning
confidence: 99%
“…In principle, CE is a procedure that can only be performed in the fasting state [10]. In order to improve observational yield, diagnostic yield, and the large bowel arrival rate, a number of studies have been conducted using a variety of preparations (table 4) [5,6,7,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30]. However, studies evaluating the efficacy of MC as bowel preparation are currently very limited in number [22,24].…”
Section: Discussionmentioning
confidence: 99%